2015
DOI: 10.1007/s10948-015-3112-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Morphological Studies of Copper-Doped Nickel Ferrite

Abstract: Ferrite nanocrystals are an interesting material due to their rich physical properties. Here we add non-magnetic dopant Cu to nickel ferrite nanocrystals, Ni 1−x M x Fe 2 O 4 (x = 0.2, 0.4, and 0.6) M = Cu, and study how relevant properties of the samples are modified accordingly. The grain size and the surface morphology were studied by scanning electron microscopy (SEM).Basically, these doping cause a rearrangement of Fe +3 ions into the two preexisting octahedral and tetrahedral sites. In fact, this, we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Cu 2+ is a highly electrically conductive Jahn-Teller ion in the ground state with degenerate orbitals that are influenced by the distortion. The crystal distortions are caused by the incorporation of Cu 2+ ions in the spinel ferrites, which is directly linked with enhancement in electrical and magnetic properties [16][17][18]. It has been reported that the crystal distortion caused by Cu 2+ ions depend on their occupancy at tetrahedral and octahedral sites [19].…”
Section: Introductionmentioning
confidence: 99%
“…Cu 2+ is a highly electrically conductive Jahn-Teller ion in the ground state with degenerate orbitals that are influenced by the distortion. The crystal distortions are caused by the incorporation of Cu 2+ ions in the spinel ferrites, which is directly linked with enhancement in electrical and magnetic properties [16][17][18]. It has been reported that the crystal distortion caused by Cu 2+ ions depend on their occupancy at tetrahedral and octahedral sites [19].…”
Section: Introductionmentioning
confidence: 99%
“…044-1485) and CuFe 2 O 4 (JCPDS No. 77-0010) which shows that the synthesis of CuNiFe 2 O 4 nanospheres is well performed 76. EDS analysis displays the presence of Fe, Cu, Ni and O elements with 21.16, 12.85, 11.48 and 36% weight percent (Fig.S3).Electrochemical test.-Performance of the electrodes.-The electrochemical behaviour of the 1 mM K 3 [Fe(CN) 6 ]/K 4 [Fe(CN) 6 ] in the existence of 0.1 M KCl (as probe solution) on the surface of the developed electrodes contributes to the study of the performance of the electrodes and the suitability of an electrode for designing an electrochemical sensor.…”
mentioning
confidence: 86%
“…The suspension was filtered, given three acetone washes, and then dried at 80 C. [36] It is well known that ferrite materials morphological changes and size significantly affect how their physical characteristics are governed. [37,38] As a result, many methods for synthesizing copper ferrite nanoparticles are explored in the current work. The information in Table 1 displays the temperature different at which the nanoparticle was calcified as well as the size and shape of the produced CFs.…”
Section: Polyol Routementioning
confidence: 99%